Roasted Nigella Sativa Seed As A Functional Ingredient In Foods And Beverage– Exploratory Studies - Varastegani, Boshra (2021)
Nigella sativa also known as black cumin or black seed is extensively used for culinary purposes in many parts of the world. Upon roasting and grinding the seed appears dark brown with aroma and taste similar to roasted coffee bean. Since the roasted seed is rich in caffeine and bioactive compounds, the potential for utilizing it as a powdered coffee-like beverage product can be tremendous. In addition, the seed extracts could be developed into a nutraceutical product or used as a functional additive in food.